2014
DOI: 10.2147/ijwh.s54269
|View full text |Cite
|
Sign up to set email alerts
|

Risk of spontaneous preterm birth in relation to maternal experience of serious life events during pregnancy

Abstract: BackgroundThe purpose of this study was to examine the risk of preterm birth (PTB) in relation to serious life events experienced during pregnancy in Peruvian women.MethodsThis case-control study included 479 PTB cases and 480 term controls. In-person interviews asked information regarding sociodemographics, medical and reproductive histories, and serious life events experienced during pregnancy. Multivariate logistic regression procedures were used to estimate adjusted odds ratios (ORs) and 95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
1
18
0
4
Order By: Relevance
“…The relation between prenatal stress and prematurity is complex and likely influenced by timing and degree of maternal perceived stress, type of stressor [20] [21] and maternal coping mechanisms, and maternal race or ethnicity. For example, exposure to an earthquake (a traumatic event) has been associated with preterm birth only when such exposure occurred during the first trimester of pregnancy [22].…”
Section: Prenatal Stress and Prematuritymentioning
confidence: 99%
“…The relation between prenatal stress and prematurity is complex and likely influenced by timing and degree of maternal perceived stress, type of stressor [20] [21] and maternal coping mechanisms, and maternal race or ethnicity. For example, exposure to an earthquake (a traumatic event) has been associated with preterm birth only when such exposure occurred during the first trimester of pregnancy [22].…”
Section: Prenatal Stress and Prematuritymentioning
confidence: 99%
“…A report from Peru revealed that prenatal serious life events caused more than a twofold increased risk of preterm birth (OR 2.29, 95% CI 1.65-3.18) and the magnitude of the association increased with the increased frequency of serious life events (p trend , 0.001). 23 Another report from China revealed that risk of preterm birth increased with higher prenatal serious life events during the first trimester (OR 2.40, 95% CI 1.13-5.09) and second trimester (OR 2.86, 95% CI 1.26-6.47). 18 The reason for different findings in this study may be that the impact of stressful life events varies depending on lifestyle, culture, intent of stressor, timing of stressor, and self-perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 But this possibility is relevant only insofar as the difference in outcomes of birth at 28 and 30 weeks is significant. Are the increased risks associated with being born at 28 weeks versus 30 weeks sufficiently weighty to override the presumption that we must tell the mother?…”
Section: Professor Daniel Groll and Nabina Liebow Respondmentioning
confidence: 99%